Time from Diagnostic Suspicion to In-Person Evaluation in Skin Cancer Using Teledermatology - Fuenzalida-Cruz, H; Loubies-Muñoz, R (Mary Ann Liebert Inc., 2025)
Introduction: Early diagnosis of skin cancer is crucial for improving prognosis. Teledermatology (TD) usage can optimize referrals and reduce waiting times. This study aims to evaluate waiting times at the critical referral nodes in teleinterconsultations that raised suspicion of skin malignancy in the Chilean TD platform of the public health care system. Materials and Methods: A cross-sectional observational study that analyzed asynchronous teleinterconsultations and raised suspicion for skin malignancy following the teledermatologist evaluation was uploaded on the Chilean Ministry of Health’s TD platform from January 1 to June 30, 2022. Results: Out of 20,522 teleinterconsultations, 1,853 raised suspicion of skin cancer. Among them, 1,119 patients were assessed by in-person examination, while 669 were still on the waiting list. Response times averaged 3.98 days for TD diagnostic suggestions. Overall referral times averaged 75.98 days from initial teleinterconsultation to the final specialist in-person evaluation. Waiting times showed significant differences among health care services and geographic regions. Discussion: In resource-limited settings, TD serves as a valuable tool to optimize referrals and manage the demand for oncologic dermatological consultation. The long waiting times emphasize the need for targeted interventions, especially in regions with longer delays. Conclusion: While TD has shown to be an effective tool in optimizing referrals, waiting times still exceed international recommendations, even in urban centers. The considerable heterogeneity in referral times within health care services and geographic regions highlights the necessity of establishing standardized referral protocols and explicit deadlines to fulfill teleinterconsultations that raise suspicion of skin malignancy in the Chilean public system. © 2025, Mary Ann Liebert, Inc., publishers.